Proses Pembentukan dan Asal Material Formasi Kayasa di Halmahera Berdasarkan Unsur Jejak dan Unsur Tanah Jarang - Irzon, Ronaldo (BRIN Publishing, 2019)
The complexity of rock formation on Halmahera Island is influenced by convergences of at least three main plates and is located in the active collision of two arcs. The Kayasa Formation is one of four volcanic rock units on Halmahera Island. Petrographic analysis, rare elements, and rare earth elements (REE) are applied in studying the rock emplacement process and the material source of Kayasa Formation. Bipolar microscopy is utilized in petrographic studies while Inductively Coupled Plasma-Mass Spectrometry is used for measuring the trace and rare earth elements compositions in seven fresh samples and four altered/weathered rocks in Kayasa Formation’s domain. The fresh samples are classified as andesite-basalt based on quartz, K-feldspar, and plagioclase modal composition. Plagioclase fractional crystallization is thought to play an important role in the crystallization of Kayasa Formations. Fresh rocks in this study tend to crystallize under oxidative conditions in the marine environment, whilst altered or weathered ones formed in a reductive environment above sea level. Based on megascopic observations and REE patterns, the material of Kayasa Formation is very likely derived from the ocean plate.